Identification of chromatin accessibility domains in human breast cancer stem cells. (1st March 2016) - Hardy, K.; Wu, F.; Tu, W.; Zafar, A.; Boulding, T.; McCuaig, R.; Sutton, C.R.; Theodoratos, A.; Rao, S.
ABSTRACT: Epithelial-to-mesenchymal transition (EMT) is physiological in embryogenesis and wound healing but also associated with the formation of cancer stem cells (CSCs). Many EMT signaling pathways are implicated in CSC formation, but the precise underlying mechanisms of CSC formation remain elusive. We have previously demonstrated that PKC is critical for EMT induction and CSC formation in inducible breast EMT/CSC models. Here, we used formaldehyde-assisted isolation of regulatory elements-sequencing (FAIRE-seq) to investigate DNA accessibility changes after PKC activation and determine how they influence EMT and CSC formation. During EMT, DNA accessibility principally increased in regions distant from transcription start sites, low in CpG content, and enriched with chromatin enhancer marks. ChIP-sequencing revealed that a subset of these regions changed from poised to active enhancers upon stimulation, with some even more acteylated in CSCs. While regions with increased accessibility were enriched for FOX, AP-1, TEAD, and TFAP2 motifs, those containing FOX and AP-1 motif were associated with increased expression of CSC-associated genes, while those with TFAP2 were associated with genes with increased expression in non-CSCs. Silencing of 2 members of the FOX family, FOXN2 and FOXQ1, repressed CSCs and the mesenchymal phenotype and inhibited the CSC gene signature. These novel, PKC-induced DNA accessibility regions help explain how the epigenomic plasticity of cells undergoing EMT leads to CSC gene activation.